Analysis of wind power potentials at abandoned mine promotion districts in Korea. Issue 2 (3rd March 2016) - Song, Jinyoung; Choi, Yosoon
Abstract: This study assessed the wind power potentials at seven abandoned mine promotion districts in Korea. The wind power system with a capacity of 2 MW was considered at each district. The meteorological data measured by National Institute of Meteorological Research in Korea were used to determine the representative values of wind data at each district. The estimated electric power productions and economic effects of wind power systems were analyzed using RETScreen software developed by Natural Resources Canada. The results showed that the Taebaek district has the highest wind power potential where the estimated electric power production is about 3642 MWh/year, the net present value is 8984 million KRW, and the payback period is about 5.3 years.